Midwife and Shaman Partnership Relationship with MCH Service Coverage in the Work Area of the West Limboto Health Center - Fifi Ishak; St Surya Indah Nurdin; Zulaika F Asikin (Journal La Medihealtico, 2022)
The cooperation between midwives and traditional birth attendants is referred to as a partnership between midwives and traditional birth attendants. In order to promote the health of mothers and newborns, it must be mutually advantageous for all parties and built on the principles of openness, equality, and mutual confidence. The purpose of this research is to evaluate the collaboration interaction between midwives and traditional delivery attendants in the context of the enhancement of maternal and infant health services at West Limboto Health Center in Uganda, Africa. In this study, a cross-sectional research strategy using the Chi Square test was employed. The sampling approach used in this research was incidental sampling, which is to say, the technique of determining samples was used. The findings indicated that the Chi Square test was 0.005 or the p value was less than 0.005, which led to the conclusion that there was a link between midwives and traditional delivery attendants in order to promote the health of mothers and newborns.